(untitled) (Archaeologia Adriatica, 2007)
The recently completed systematic excavations of the early Neolithic site of Crno Vrilo near Zadar have supplemented to a considerable extent the previously existing gaps in knowledge of this chronological segment of the Neolithic in the eastern Adriatic, and in terms of the abundance and diversity of the finds, this site has proven to be one of the most characteristic early Neolithic agglomerations in the eastern Adriatic, with all features quite appropriate for a social community from this period of prehistory. Although in terms of the chronological and developmental ranking of sites of the early Neolithic in the eastern Adriatic it does not belong to the very beginning of this period, questions relating to this shall be addressed in this article. There are several reasons for this, but only a few basic ones will be listed here. First. In the recent period, such problems have again gained a predominant place among questions related to this prehistoric period in the eastern Adriatic region, and it is natural that each new investigation into the early Neolithic, whether or not it encompasses its very beginnings or somewhat later chronological and developmental segments, inherently implies inclusion in this discussion. Second. A quite significant number of researchers who have addressed these questions in recent years, either as primary or secondary problems in a broader spatial context, have approached these themes from varied positions, and consequently the suggested solutions are quite divergent, and sometimes even completely opposed.